2021
DOI: 10.4067/s0718-50062021000300085
|View full text |Cite
|
Sign up to set email alerts
|

Educar para el desarrollo sostenible en el contexto universitario: un análisis bibliométrico

Abstract: El objetivo de esta investigación es analizar la productividad científica sobre la educación para el desarrollo sostenible en la educación superior. Los conflictos ecológicos constituyen uno de los fenómenos de mayor trascendencia para la humanidad. Todo ello repercute en los espacios educativos, reclamándose una educación comprometida con el respeto al planeta en todos los niveles formativos, incluido el universitario. Se emprende un estudio bibliométrico a partir de la revisión de 322 artículos científicos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
2
0
6
Order By: Relevance
“…Throughout these phases, to date, there is a long research background demonstrating the interest that the scientific community has shown around the revision and establishment of the conceptual and methodological bases of ESD in the university scope (Amaral et al, 2015;Caride and Meira 1998;Ferrer-Balas, Buckland, and De Mingo 2009;González-Gaudiano 2005;González-Gaudiano and De Alba-Ceballos 1994;Leal-Filho 2011;Lele 2017;Limón 2006;Lozano et al 2015;Novo 2009;Tilbury 1995;Waas, Verbruggen, and Wright 2010;Wright 2002;2006;Xiong et al, 2013) and the development of specific research lines, such as environmentalisation and/or curricular sustainability (Junyent and de Ciurana 2008;Watson et al 2013;Wemmenhove and de Groot 2001), faculty training (Aznar et al 2018;Calafell and Junyent 2017;Gough 2016;Solis-Espallargas and Valderrama-Hernández 2015), the establishment of key competences (García-Esteban and Murga-Menoyo 2015;Roorda 2019;Sánchez Carracedo et al 2018;Sims and Falkenberg 2013;Vare et al 2019;Wiek, Withycombe, and Redman 2011), and the implementation of sustainability approaches, methodologies and projects carried out in the university scope (Aramburuzabala, Cerrillo, and Tello 2015;Tamura and Uegaki 2012), as is reflected in the bibliometric analyses performed (Alcalá del Olmo-Fernández et al 2021;Toscano, Fuentes, and Fajardo 2019) and the extensive literature in this respect. Likewise, it is of necessary reference to create networks in the different regions of the world, together with the commitment and work that has been developed since the 1990s with respect to the inclusion of s...…”
Section: Justificationmentioning
confidence: 99%
“…Throughout these phases, to date, there is a long research background demonstrating the interest that the scientific community has shown around the revision and establishment of the conceptual and methodological bases of ESD in the university scope (Amaral et al, 2015;Caride and Meira 1998;Ferrer-Balas, Buckland, and De Mingo 2009;González-Gaudiano 2005;González-Gaudiano and De Alba-Ceballos 1994;Leal-Filho 2011;Lele 2017;Limón 2006;Lozano et al 2015;Novo 2009;Tilbury 1995;Waas, Verbruggen, and Wright 2010;Wright 2002;2006;Xiong et al, 2013) and the development of specific research lines, such as environmentalisation and/or curricular sustainability (Junyent and de Ciurana 2008;Watson et al 2013;Wemmenhove and de Groot 2001), faculty training (Aznar et al 2018;Calafell and Junyent 2017;Gough 2016;Solis-Espallargas and Valderrama-Hernández 2015), the establishment of key competences (García-Esteban and Murga-Menoyo 2015;Roorda 2019;Sánchez Carracedo et al 2018;Sims and Falkenberg 2013;Vare et al 2019;Wiek, Withycombe, and Redman 2011), and the implementation of sustainability approaches, methodologies and projects carried out in the university scope (Aramburuzabala, Cerrillo, and Tello 2015;Tamura and Uegaki 2012), as is reflected in the bibliometric analyses performed (Alcalá del Olmo-Fernández et al 2021;Toscano, Fuentes, and Fajardo 2019) and the extensive literature in this respect. Likewise, it is of necessary reference to create networks in the different regions of the world, together with the commitment and work that has been developed since the 1990s with respect to the inclusion of s...…”
Section: Justificationmentioning
confidence: 99%
“…En este sentido, según Martínez Lirola (2018), optar por una educación sostenible implica potenciar el pensamiento crítico y que las personas asuman un compromiso como ciudadanía activa y comprometida con la construcción de un mundo mejor. Desde este enfoque del proceso formativo, se concede importancia a la idea de transformación social (Alcalá del Olmo-Fernández et al, 2021;Aleixo et al, 2018), ya que, la educación para el desarrollo sostenible se centra especialmente en el uso adecuado de recursos de los que se dispone y el respeto al medio ambiente. Por tanto, nos encontramos ante una propuesta formativa que potencia la necesidad de cambio y un emprendimiento sostenible, aspectos esenciales para que se pueda avanzar en justicia social, que es, sin duda, uno de los retos fundamentales del siglo XXI (Benavides-Sánchez et al, 2021).…”
Section: Discussionunclassified
“…En consecuencia, organismos como la Unesco, aunados a los ODS, actúan como un horizonte pedagógico que guía la modificación de los patrones de producción de conocimiento. Es así que, mediante un modelo transversal de educación, se apuesta por una pedagogía más ética y humana, que transmita los valores de justicia, equidad y responsabilidad (Alcalá et al, 2021).…”
Section: Ronald Madera Terán | Ronald Rusbell Madera Arnao | Yeni Mad...unclassified